2012
DOI: 10.1097/meg.0b013e328355cfd0
|View full text |Cite
|
Sign up to set email alerts
|

Liver hepcidin mRNA expression is inappropriately low in alcoholic patients compared with healthy controls

Abstract: Hepcidin liver expression is inappropriately low in alcoholic patients with active alcoholism and preserved hepatic function, and we conclude that this is the mechanism for alcohol consumption-associated iron overload in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…31 In the present study, %SAT predicted early mortality and also correlated with incidence of organ failure in ACLF patients, which suggests its potential as a prognostic marker in these patients. Various studies in the past have shown an inverse correlation of serum hepcidin with tissue iron in patients with CLD, 32,33 but none pertaining to ACLF. Taken together, our data highlight the importance of dysregulated iron homeostasis, which correlates with disease severity in patients with ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…31 In the present study, %SAT predicted early mortality and also correlated with incidence of organ failure in ACLF patients, which suggests its potential as a prognostic marker in these patients. Various studies in the past have shown an inverse correlation of serum hepcidin with tissue iron in patients with CLD, 32,33 but none pertaining to ACLF. Taken together, our data highlight the importance of dysregulated iron homeostasis, which correlates with disease severity in patients with ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol has been shown to decrease hepcidin expression, which could lead to increased iron absorption and recycling (23). Both in vitro and human studies have described that alcohol suppressed hepcidin transcription in the liver and may protect from iron deficiency (24). However, alcohol intake was unlikely to be a major factor on hepcidin levels in this study, given that excessive alcohol consumption was an exclusion criterion for all NASH CRN studies (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Each sample was reverse transcribed into cDNA using SuperScript II Reverse Transcriptase (Invitrogen). Gene expression was quantified by means of the comparative Ct method (ΔΔCt) and the relative quantification (RQ) was calculated as 2 −ΔΔCt [2123]. Relative mRNA levels of E-CA, α -SMA, smad3, smad7, Col IV, and FN were examined and normalized to β -actin mRNA.…”
Section: Methodsmentioning
confidence: 99%